Evgenii Kharitonov and the Aesthetics of Sousveillance - Ogden, Dylan (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2026)
This article analyzes the fiction of the Russian author Evgenii Kharitonov through the lens of Steve Mann’s (2013) theorization of “sousveillance” and Édouard Glissant’s (2010) conception of the right to opacity. As a gay man and dissident writer, Kharitonov was under observation by the KGB throughout his life, and his stories frequently confront the inherent violence of homophobic surveillance in the Soviet Union. However, this article demonstrates how Kharitonov actively resists Soviet surveillance by drawing attention to the performance of gay invisibility that it enforces and challenging the implicit conceptions of homosexuality that it entails. Through a close reading of several short stories from his collection, Under House Arrest [Pod domashnim arestom] (1998), I argue that Kharitonov’s stories use strategies of sousveillance to explore the opaque spaces where gay communities could exist outside the visibility and conceptual legibility of official surveillance.